Congenital interparietal encephalocele with porencephlacic cyst: A case report - Berihu Tadishu, MD; Seare Halefom Kahsay, MD; Samson Yibalih, MD; Yirgalem Teklebirhan, MD (Radiology Case Reports)
Parietal encephalocele is a rare congenital condition involving herniation of brain matter through skull openings. Although isolated cases are reported, concurrent parietal encephalocele with porencephalic cyst is exceptionally rare. A 45-day-old infant presented with parietal scalp swelling since birth. Imaging revealed parietal encephalocele with porencephalic cyst. The encephalocele was surgically repaired with a favorable outcome, while the associated porencephalic cyst was managed conservatively. Preoperative neuroimaging is essential to evaluate the lesion and identify any associated brain abnormalities.